2020
DOI: 10.3390/min10080711
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pollutants from an AMD from a Coal Mine by Neutralization/Precipitation Followed by “In Vivo” Biosorption Step with the Microalgae Scenedesmus sp.

Abstract: This work evaluates the benefits of a complementary treatment step of acid mine drainage (AMD) using the algae Scenedesmus sp. in terms of algae biomass production, residual metal removal, and the toxicity of the discharged water. Conventional treatment by neutralization/precipitation of an AMD from a coal mine in Brazil was conducted with Ca(OH)2 at pH 8.7. Algal growth studies were performed in the treated AMD, with and without a nutrient supply. The raw effluent and treatments were compared in terms of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, the high ash content is notable, which is at the maximum threshold of that found in algae [39]. This is possibly due to the assimilation of inorganic components from the mine water [12,40]. If the values are normalized to only organic components, as demonstrated in many studies, the composition becomes 15.1% total lipids, 34% proteins, and 50.9% carbohydrates.…”
Section: Microalgae Biomass Productionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, the high ash content is notable, which is at the maximum threshold of that found in algae [39]. This is possibly due to the assimilation of inorganic components from the mine water [12,40]. If the values are normalized to only organic components, as demonstrated in many studies, the composition becomes 15.1% total lipids, 34% proteins, and 50.9% carbohydrates.…”
Section: Microalgae Biomass Productionmentioning
confidence: 92%
“…The treated water is clear and some ionic species are suitable as a source of essential nutrients for algae growth, such as Ca 2+ , Zn 2+ , Mn 2+ , and SO 4 −2 [7,10], although the addition of other nutrients may be necessary. In a previous study [12], the algae Scenedesmus sp. was grown in treated acid mine drainage from coal mining.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Over the last few decades, algae-based systems have shown promising prospects for removing various heavy metals from AMD. Algae function as “hyper-accumulators” (when an active mechanism is involved) and “hyper-adsorbents” (through passive mechanisms), with a pronounced selectivity for different elements [ 211 , 212 ]. Microalgal species such as Spirulina sp., Chlorella , Chlamydomonas , Scenedesmus , Cladophora , and Oscillatoria are widely employed for heavy metal removal [ 212 , 213 , 214 , 215 ].…”
Section: Coal Microalgae Hold Great Biotechnological Potential In Coa...mentioning
confidence: 99%
“…The papers by Zawierucha et al [30], Kato et al [31], Ryskie et al [32], and Santos et al [33] were related to diverse processes and tools for the treatment of AMD. Zawierucha et al [30] showed a novel approach based on the selectivity of elements of environmental concern, especially arsenic.…”
mentioning
confidence: 99%